Cellular uptake of Nigella sativa oil-PLGA microparticle by PC12 cell line - Doolaanea, Abd Almonem; Mansor, Nur 'Izzati; Mohd Nor, Nurul Hafizah; Mohamed, Farahidah (Informa UK Ltd, 2014)
The aim of this study is to investigate the cell uptake of Nigella sativa oil (NSO)-PLGA microparticle by neuron-like PC-12 cells in comparison to surfactants; hydrophilic (Tween 80 & Triton X100) and hydrophobic (Span 80). Solvent evaporation was used to precisely control the size, zeta potential and morphology of the particle. The results revealed varying efficiencies of the cell uptake by PC-12 cells, which may be partially attributed to the surface hydrophobicity of the microparticles. Interestingly, the uptake efficiency of PC-12 cells was higher with the more hydrophilic microparticle. NSO microparticle showed evidence of being preferably internalised by mitotic cells. Tween 80 microparticle showed the highest cell uptake efficiency with a concentration-dependent pattern suggesting its use as uptake enhancer for nonscavenging cells. In conclusion, PC-12 cells can take up NSO-PLGA microparticle which may have potential in the treatment of neurodegenerative disease.